REDESAIN TAMAN CAHAYA MADANI GAYUNG BERSAMBUT DI KOTA SINGKAWANG - Akmal, Muhammad Daffa Dhia; affrilyno, affrilyno; Purnomo, Yudi (JMARS: Jurnal Mosaik Arsitektur, 2025)
Singkawang is a city in West Kalimantan known as the “City of Tourism,” enriched by the arts, culture, and traditions of three major ethnic groups: Chinese, Dayak, and Malay. This diversity serves as an essential foundation for developing public spaces that accommodate various community activities while strengthening social interaction. One of the most strategic public spaces is the city park, which functions not only as a recreational area but also as a hub for social, cultural, educational, and environmental activities. The redesign of Cahaya Madani Gayung Bersambut Park is carried out to address the limited availability of public spaces in Singkawang. The park is envisioned as a facility that can accommodate recreational activities, art performances, exhibitions, as well as environmental and cultural education. Beyond enhancing the city’s visual appeal, the park is also expected to maintain ecological balance and serve as a learning space for visitors. The aim of this proposed design is to redevelop Cahaya Madani Park into a supporting facility that meets the needs of the community and cultural activities in Singkawang through stages of analysis, synthesis, evaluation, and iterative improvement. Located in a strategic area, the park is expected to become a new inclusive, multifunctional, and sustainable landmark that can be enjoyed by all segments of society and tourists.